Competitiveness of the Garment Industry on the Basis of the Industrial Cluster Establishment - Sinyavets, Tatiana Dmitrievna; Rodina, Larisa Aleksandrovna (Economy of Regions, 2016)
The issue of the development prospects of the Russian economy and the economy of its individual branches in the regions is highly relevant in terms of the increasing crises and economic development challenges. The scope of the study is a garment industry of the Siberian Federal District, which includes 12 subjects, and only six of them develop the garment industry actively. There are the regions of Kemerovo, Novosibirsk, Omsk, Tomsk, Krasnoyarsk Krai and the Republic of Khakassia. The subject matter of the research is the state and prospects of the garment industry of the Siberian Federal District. It also includes the assessment of the garment industry as one of the sub-sectors of the light industry in terms of its competitiveness in the domestic market. The purpose of the comprehensive study is to determine the conditions and factors affecting the development of the industry, as well as to identify its development reserves and competitiveness on the basis of industrial clusters generation. The hypothesis of this study is that in the Siberian Federal District, there are a need and reserves to create a cluster of the garment industry. The main methods of the study are the comparative analysis, the expert assessment of the sector in certain regions of the Siberian Federal District, as well as the assessment of possible formation of the industrial cluster in the region. The results of the study are the evaluation of the competitiveness and prospects of the garment industry in Russia and the Siberian Federal District (a low level of development and competitiveness); the evaluation of the development level of the garment industry in the Federal District, which have showed the demand for apparel products from the population and enterprises, as well as the conditions for the provision of clothing manufacture with natural fabrics and synthetic materials, labor resources and research and development achievements; also the justification of the existing potential for development of a sectoral cluster by means of pooling together the productions and economic communications of the Novosibirsk and Omsk regions at the initial stage. The obtained results should be used to strengthen works for the development of regional industrial cluster (with a creation of a working group at the regional governments, the garment industry development programs, and practical measures for its realization), as well as a creation of conditions for stimulation of investment activity of entrepreneurs. The research has confirmed the hypothesis, that in the Siberian Federal District, there are a need and reserves to create a cluster of the garment industry.